-3kx^2=-2x^3-4x+11
divide each side by -3x^2
k=(2/3)x+(4/3x)-(11/3x^2)
Find the value of k p(x)=2x^3-3kx^2+4x-5=6
2 answers
2 x³ - 3 k x² + 4 x - 5 = 6 Subtract 6 to both sides
2 x³ - 3 k x² + 4 x - 5 - 6 = 6 - 6
2 x³ - 3 k x² + 4 x - 11 = 0 Add 3 k x² to both sides
2 x³ - 3 k x² + 4 x - 11 + 3 k x² = 0 + 3 k x²
2 x³ + 4 x - 5 - 6 = 3 k x²
3 k x² = 2 x³ + 4 x - 11 Divide both sides by 3 x²
k = ( 2 x³ + 4 x - 11 ) / 3 x²
2 x³ - 3 k x² + 4 x - 5 - 6 = 6 - 6
2 x³ - 3 k x² + 4 x - 11 = 0 Add 3 k x² to both sides
2 x³ - 3 k x² + 4 x - 11 + 3 k x² = 0 + 3 k x²
2 x³ + 4 x - 5 - 6 = 3 k x²
3 k x² = 2 x³ + 4 x - 11 Divide both sides by 3 x²
k = ( 2 x³ + 4 x - 11 ) / 3 x²